(untitled) (Journal Of Educational and Psychological Researches, 2012)
There Are Many Communities Suffering Of Unemployment Due To Has Great Social And Economic Impact, As Well As The Psychological Effects Devastating And Serious And That May Threaten States With Collapse And Leading Human Displacement And Loss And Crime, And Often Derive Unemployed People To Practice Bad Habits Such As Gambling, Alcohol And Drug Abuse To Escape From Their Reality To Their Concerns And Problems. It Should Be Noted, That The Largest Percentage Of Unemployment In Developing Societies Represented By The Educated Class Of University Graduates, And This Is Something Painful. The Unemployed Know That (Each Capable Of Working And Who Want To Look For And Accept Prevailing Bricks) Is The Individual Unemployed In The Case Of The Following Situations: 1 - Completed Education Or Training Did Not Find A Job. 2 - Ended His Employment Contract Did Not Find Another Job. 3 - Waived His Services Before The End Of His Contract And Did Not Find A Job. 4 - Working Less Than (14) Hours Per Week. We Will Look At This Research To The Types Of Unemployment And To Their Causes And Then To The Psychological And Social Effects. In Terms Of Processors, There Are Several Treatments For States To Eliminate Or Reduce Unemployment, Namely: 1 - To Encourage Capital Only Pleural Investment By Providing Facilities And Guarantees. 2 - Reduce Taxes On Large Projects That Are Running A Large Number Of Workers. 3 - Supporting Agriculture Through Processing Farmers Fertilizers And Seeds. 4 - Encourage Small Businesses By The State. Finally Prepare A National Program To Combat Graduate Unemployment By Forming The Central Department For Operation Distributes Unemployed Ministries According To Certain Mechanisms.